Diurnal cycle in convergence patterns in the boundary layer east of the Andes and convection - Nicolini, Matilde (2011)
The South American Low-Level Jet Experiment (SALLJEX) provided a unique dataset to investigate the existence of a mesoscale low-level circulation and of a diurnal cycle in its related convergence pattern over the Southeastern South American region east of the Andes, as well as its relationship with deep convection during the warm season. The present paper builds upon high-resolution analyses produced, assimilating the data collected during the SALLJEX field campaign using BRAMS, and explores their capability to reproduce mesoscale circulations not resolved by the low density observational network available in this region. Results of the analyses show a diurnal oscillation signal in the mean boundary layer convergence pattern over the plains with a nocturnal (daytime) convergence (divergence) maximum. These results are coherent with previous findings of a nocturnal phase in the mature stage of organized deep convection and related precipitation in subtropical latitudes east of the Andes during the warm season. The diurnal cycle of convergence/divergence in the boundary layer is described over a 15-day period, during which different synoptic conditions occurred. During weakly forced environments a regime characterized by nocturnal eastward anomaly flow and convergence and daytime westward anomaly flow and divergence related to a mesoscale northwestern mountain-central plain flow regime dominates over the plains between the Andes Mountains, the Parana River Valley, and the southern Brazil mountain range. In contrast, during synoptic conditions dominated by the presence of a deep thermal low over northwestern Argentina and a related low-level jet, convergence at night is mainly accomplished by the predominantly meridional low-level jet, which exhibits an anomalous weak wind speed diurnal cycle with respect to its summer climatological mean. On the other hand daytime divergence is completely produced by the zonal wind component as in the previous synoptic situation. Mesoscale circulations are altered (still effecting mean divergence in the domain, which exhibits a diurnal oscillation) upon the initiation of deep convective circulations in the evening in an increasingly convectively unstable atmosphere driven by a persistent horizontal advection of heat and moisture at low levels and forced by convergence generated by the low-level jet and the presence of a frontal zone. Convection intensifies at night when its related convergence over the plains comes in phase with the convergence related to the nocturnal maximum in the low-level jet.